An experimental study: An integrative strategy of PBL combined with an organ-systems-based curriculum to improve academic achievement and career maturity - Yao, Cheng; Yang, Yu; Yu, Siliang (Asian Journal of Education and Training, 2023)
This study aims to investigate the impact of integrating Problem-Based Learning (PBL) and Organ System-Based Curriculum (OSBC) on medical students’ academic achievement and career maturity within the context of medical education. An experimental design was employed, involving students from a medical school in China. Participants were randomly assigned to either a control group with a traditional curriculum or an experimental group receiving an integrated PBL and OSBC curriculum focused on cardiovascular system diseases. The intervention spanned four weeks. The results indicate that the experimental group demonstrated significantly higher academic achievement immediately after the intervention compared to the control group. This improvement persisted in a follow-up test conducted one month later. Career maturity also improved in the experimental group, albeit with a less sustained effect. The study underscores the potential of integrated teaching strategies in medical education for enhancing critical thinking and practical skills. However, long-term improvements in career maturity may necessitate further refinement of teaching methods. These findings contribute to the ongoing discourse on effective medical education strategies and emphasize the importance of a comprehensive approach to prepare students for academic excellence and clinical competence. Future research with larger sample sizes and consideration of additional influencing factors is recommended to gain deeper insights into the dynamics of medical education.